Low Cognitive Load and Reduced Arousal Impede Practice Effects on Executive Functioning, Metacognitive Confidence and Decision Making - Jackson, Simon A. (PLoS One, 2014)
The present study investigated the effects of low cognitive workload and the absence of arousal induced via external physical stimulation (motion) on practice-related improvements in executive (inhibitory) control, short-term memory, metacognitive monitoring and decision making. A total of 70 office workers performed low and moderately engaging passenger tasks in two successive 20-minute simulated drives and repeated a battery of decision making and inhibitory control tests three times – before, between and after these drives. For half the participants, visual simulation was synchronised with (moderately arousing) motion generated through LAnd Motion Platform, with vibration levels corresponding to a well-maintained unsealed road. The other half performed the same simulated drive without motion. Participants’ performance significantly improved over the three test blocks, which is indicative of typical practice effects. The magnitude of these improvements was the highest when both motion and moderate cognitive load were present. The same effects declined either in the absence of motion (low arousal) or following a low cognitive workload task, thus suggesting two distinct pathways through which practice-related improvements in cognitive performance may be hampered. Practice, however, degraded certain aspects of metacognitive performance, as participants became less likely to detect incorrect decisions in the decision-making test with each subsequent test block. Implications include consideration of low cognitive load and arousal as factors responsible for performance decline and targets for the development of interventions/strategies in low load/arousal conditions such as autonomous vehicle operations and highway driving.